2019
DOI: 10.1016/j.anr.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Agreement on Core Components of an E-Learning Cultural Competence Program for Public Health Workers in South Korea: A Delphi Study

Abstract: Purpose: This study aimed to seek agreement on the core components of an e-learning cultural competence program for Korean public health workers (PHWs) while prioritizing educational content areas. Methods: A two-round Delphi study was performed with 16 Korean experts from five disciplines. Data were collected between August 30 and November 24, 2017. A questionnaire was developed from literature reviews and previous focus group interviews concerning PHWs. The panel members were asked to rate the importance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…This format allowed the Delphi study to be conducted in a reduced time frame when compared with previous studies, a frequently recognised deficiency of this technique. 6 We had a high engagement, compared with previous Delphi studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This format allowed the Delphi study to be conducted in a reduced time frame when compared with previous studies, a frequently recognised deficiency of this technique. 6 We had a high engagement, compared with previous Delphi studies.…”
Section: Discussionmentioning
confidence: 93%
“…We developed a novel technique, a live Delphi study, to seek consensus on the skills and competencies a new ENT ST3 should possess. This format allowed the Delphi to be conducted in a reduced time frame when compared to previous studies -a frequently recognised deficiency of this technique (6). We had a high engagement, compared to previous Delphi studies,…”
Section: Discussionmentioning
confidence: 99%
“…There has been a considerable shortage of evidence regarding whether cultural competence education delivered to health professionals can change patient and organizational outcomes (Chae et al., 2019). Although this study did not measure the same group of migrants repeatedly, it showed that improving PHWs' cultural competence increased migrant trust and satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past half‐century, public health workers have become a growing force in extending healthcare and improving people's well‐being (Perry, Zulliger, & Rogers, ). Moreover, public health workers are committed to developing disease prevention strategies, controlling disease transmission and promoting health education (Chae, Kim, Yoo, & Lee, ; Krisberg, ). As the key value of public health workers in health networks has been highlighted with the worldwide promotion of health status, their work load has been increasing.…”
Section: Introductionmentioning
confidence: 99%